2022
DOI: 10.3389/fimmu.2022.986447
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of T-cell cytotoxic marker IL18R1 promotes cancer proliferation and migration and is associated with dismal prognosis and immunity in lung squamous cell carcinoma

Abstract: Immunotherapy can improve the survival of patients with advanced lung squamous cell carcinoma (LUSC). T cytotoxic cells are one of the main members of the immune microenvironment. Herein, we aimed to identify the roles of T-cell cytotoxic markers interleukin 18 (IL18) receptor 1 (IL18R1) in the LUSC progression using bioinformatics, clinical tissue specimen, and cell experiment. We assessed the association between the IL18R1 expression and immune infiltration and IL18R1-related competing RNA network. The IL18R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Immunotherapy is a promising treatment that can improve the quality of life and survival time of cancer patients [26][27][28]. For example, Zhang et al demonstrated that combining PDCD1/CD274 inhibitors with chemotherapy improved pCR, EFS, and OS in triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is a promising treatment that can improve the quality of life and survival time of cancer patients [26][27][28]. For example, Zhang et al demonstrated that combining PDCD1/CD274 inhibitors with chemotherapy improved pCR, EFS, and OS in triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A8 expression in LUAD tissues was investigated using the t -test [ 29 ]. The diagnostic value of SLC7A8 in LUAD was analyzed by computing the area under the ROC curves.…”
Section: Methodsmentioning
confidence: 99%
“…Variables with a significance level of P<0.05 were further subjected to multivariate Cox regression analysis. Additionally, nomograms were used as a tool to evaluate the prognosis of patients with cancer [14][15][16]. Thus, nomograms were developed based on the results of the multivariate Cox regression analysis, enabling the prediction of prognosis among patients with GBM.…”
Section: Tmem150a Associated Nomogramsmentioning
confidence: 99%
“…and TMEM150A overexpression were significant predictors of poor prognosis in patients with GBM (Tables 2-4). The nomograms effectively helped visualise the prognosis and survival outcomes of patients with cancer [14][15][16]. Therefore, nomograms were constructed for OS, DSS, and PFI in patients with GBM based on the IDH status and TMEM150A expression levels (…”
Section: Plos Onementioning
confidence: 99%